THE EFFECT OF PLYOMETRIC TRAINING ON DEVELOPING THE SPEED-SPECIFIC STRENGTH OF THE UPPER AND LOWER LIMB MUSCLES AND THE ACHIEVEMENT OF YOUNG JAVELIN THROWERS - Dr. Wael Abdullah Hussein Al-lami (Proximus Journal Publishing, 2024)
The investigation aims to develop a training curriculum using the plyometric method, by studying the effect of the curriculum designed by the researcher. The researcher employed the experimental method using the equivalent groups approach to fit the research into study. The investigation's sample included young athletes participating in the Popular Mobilization Club's Track and Field Program. The researcher intended the sample to be selected deliberately, as the sample size was 4 players who were divided into two groups that were similar with regard to the studied variables (age, weight, height). Each group had two participants. Homogeneity and equivalency were employed on the studied population
Keywords: Speed-distinguished strength; plyometric; javelin throw